Pengaruh Gaya Kepemimpinan dan Kompetensi Manajerial Kepala Sekolah Terhadap Kinerja Guru - Dyah Huzaifah Cempaka; Alhadi Yan Putra; Nila Kesumawati (Journal Of Administration and Educational Management (ALIGNMENT), 2023)
This study aims to determine the effect of leadership style and managerial competence of school principals on the performance of State Middle School teachers in Kayuagung District. The research was conducted at a state junior high school in Kayuagung District. The study used a descriptive quantitative research method, with a total population of 261 teaching staff at SMP Negeri Kayuagung District, Ogan Komering Ilir Regency. The number of samples calculated using the Slovin formula obtained a sample of 72 people—data collection techniques using questionnaires, observation, and documentation. Data analysis techniques in this study used the t-test for partial tests and the F-test for simultaneous tests. The results of this study show that the principal's leadership style and managerial competence partially influence the performance of teachers of the SMP Negeri Kayuagung District. In conclusion, the principal's leadership style and managerial competence of the principal have a significant effect on teacher performance at the Kayuagung District Public Middle School Keywords: Leadership Style, Managerial Competence, Principal Teacher Performance